The Effect of Jobsheets on Students Learning Outcomes in Brick Installation Practicum - Abid Thoriq Zakiyyah; Soeparno Soeparno; Wahyu Dwi Mulyono; Muhammad Kris Yuan Hidayatulloh (APPLICATION: Applied science in Learning Research, 2026)
Student learning outcomes remained low prior to the implementation of jobsheet in the bricklaying lab. This study aims to determine the effect of the use of jobsheets on student learning outcomes in the brick installation practicum and to find out the students' response to their use in the learning process. This study uses a quantitative approach with a pretest-posttest design of one group. The subject of this research is class XI courses with a total of 30 students of the Construction and Housing Engineering Expertise Program of SMKN 1 Sidoarjo. The data collection technique includes a learning outcome test of 20 questions (pretest and posttest) and a systematically compiled student response questionnaire. Data were analyzed using paired sample t-test and percentage analysis. The results showed a significant improvement in student learning outcomes, with the average score increasing from 45.50 in the pretest to 85.33 in the posttest. The results of the hypothesis test showed a significance value of < 0.05 which means that there was a significant difference before and after the use of the jobsheet. In addition, student responses reached 79% in the positive category using a percentage scale. This shows that jobsheets are effective in improving learning outcomes and helping students understand the steps of practicum work in a systematic, directed, and more independent manner